Musik Hardcore Sebagai Media Kritik Terhadap Pemerintah: (Studi Kasus pada Band Hardcore Jember : Slugfess) - Kartika Novita Rohmah; Dicky Ahmad Fahrizi; Rheihan Alvizar; Jason Marcelino Nugroho (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This research aims to analyze the role of hardcore music as a form of criticism of a government system that is considered dilapidated. Hardcore musicians and bands often use their music as a means to express their dissatisfaction with inadequate social and political conditions. This research uses a qualitative approach to collect data through interviews with hardcore band members, analysis of song lyrics, and a review of related literature. The findings of this research indicate that hardcore music functions as a powerful medium of expression to criticize the government system which is considered corrupt and unfavorable to the people. Song lyrics and stage performances in hardcore music reflect anger, disappointment, and resistance to the injustices that exist in the government system. This research provides a deeper understanding of how hardcore music can influence individual perceptions and actions in carrying out criticism of a dilapidated government system.